2021
DOI: 10.1108/idd-10-2020-0126
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing college students’ behaviours of spreading internet public opinions on emergencies in universities

Abstract: Purpose This study aims to explore the influencing factors on college students’ behaviours of spreading Internet public opinion on emergencies in colleges and universities. This study provides a reference for these institutions to cope with and reduce the influence of Internet public opinion on emergencies and maintain their normal teaching order. Design/methodology/approach In this study, a research model by using motivation theory and design a questionnaire on the basis of relevant literature are construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…In order to improve the practical application effect of mixed teaching mode, an online and offline mixed teaching effect evaluation method based on big data analysis is proposed. e currently commonly used assessment methods based on learning inputs [4] and web-based data [6] are susceptible to interference from the external environment in the process of practical application, resulting in less accurate and less efficient assessment results. To solve such problems, we study the evaluation method of online and offline hybrid teaching effect based on big data analysis, realize the scientific evaluation of online and offline hybrid teaching effect, and optimize the hybrid teaching model based on the evaluation results to improve the hybrid teaching effect.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to improve the practical application effect of mixed teaching mode, an online and offline mixed teaching effect evaluation method based on big data analysis is proposed. e currently commonly used assessment methods based on learning inputs [4] and web-based data [6] are susceptible to interference from the external environment in the process of practical application, resulting in less accurate and less efficient assessment results. To solve such problems, we study the evaluation method of online and offline hybrid teaching effect based on big data analysis, realize the scientific evaluation of online and offline hybrid teaching effect, and optimize the hybrid teaching model based on the evaluation results to improve the hybrid teaching effect.…”
Section: Related Workmentioning
confidence: 99%
“…e evaluation method based on learning inputs in the literature [4] and the evaluation method based on network data in the literature [6] were used as the comparison methods to compare the fit between the evaluation results of this paper and the comparison methods on the research object and the set results, and the results are shown in Figure 3. It is clear from the analysis of Figure 3 that, among the three different evaluation methods, this method has the best fit with the set results, and the method of [4] has the lowest fit with the set results. is indicates that the method of this paper has high accuracy in assessing the effectiveness of online and offline hybrid teaching.…”
Section: Overall Evaluation Accuracy Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the highly developed Internet features, the network of public opinions on Chinese universities is characterized by social media disclosure, accelerated dissemination speed, diversified disseminators, and diversified dissemination methods [30]. At present, Chinese scholars mainly focus on the causes (e.g., [31]), dissemination mechanism (e.g., [32]), problems, and counter-measures (e.g., [33]) of the network's public opinions on universities.…”
Section: Crisis Management and Network Public Opinions Onmentioning
confidence: 99%
“…Research studies are being pursued in the field of IGA, the internet gaming disorder, with a focus on the personality characteristics, motives for, prevalence, predictors, diagnosis, management and prevention thereof (Demetrovics et al , 2011; Van Rooij et al , 2018; Wang et al , 2015; Kaess et al , 2014; Saunders et al , 2017; Müller et al , 2015; Ye and Liu, 2022; Palla and Sheikh, 2021).…”
Section: Introductionmentioning
confidence: 99%